2022
DOI: 10.1049/rpg2.12540
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrocarbons and renewable energies in Iran's energy matrix focusing on bioenergy: review

Abstract: Iran is one of the most potent energy exporters and fastest‐growing energy consumers in the world. Its large amount of energy exported can directly impact the economy of importer countries. Iran's energy matrix mostly consists of hydrocarbons, while the remaining portion is compounded by a blend of biofuels, hydropower, wind, solar, and other renewable sources. Even though the country has an excellent potential to reach a large amount of renewable power, it is most likely that Iran will deal with a shortage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In addition, renewable energy sources can be described as the source of energy that has been derived from natural sources that are available in nature and can be revived. In simple words, alternative energy sources can be explained as the energy sources that are obtained from those natural sources that cannot run out, for example: sunlight, wind, bio-gas and do on [9]. Utilisation or three energy sources are beneficial for the environment as this does not cause a negative impact on the environment.…”
Section: Overview Of Green Practice and Renewable Energy Sourcesmentioning
confidence: 99%
“…In addition, renewable energy sources can be described as the source of energy that has been derived from natural sources that are available in nature and can be revived. In simple words, alternative energy sources can be explained as the energy sources that are obtained from those natural sources that cannot run out, for example: sunlight, wind, bio-gas and do on [9]. Utilisation or three energy sources are beneficial for the environment as this does not cause a negative impact on the environment.…”
Section: Overview Of Green Practice and Renewable Energy Sourcesmentioning
confidence: 99%
“…A study by a number of researchers has demonstrated the importance of Iraq switching from using fossil fuels as its primary source of energy to renewable sources, particularly electricity produced from biomass. The study revealed a number of benefits connected to enhancing social, economic, and environmental issues 8 . Natural gas, in particular, dominates the production of electricity in Iraq, which is virtually entirely reliant on fossil fuels (more than 97%), according to the IEA.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed a number of benefits connected to enhancing social, economic, and environmental issues. 8 Natural gas, in particular, dominates the production of electricity in Iraq, which is virtually entirely reliant on fossil fuels (more than 97%), according to the IEA. Hydropower is the only renewable energy available in Iraq and contributes 4%.…”
mentioning
confidence: 99%
“…After the process of gasification, the producer gas is cooled and cleaned to be ready for use as fuel in gas turbines or internal combustion engines to generate electrical energy and/or thermal energy 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 After the process of gasification, the producer gas is cooled and cleaned to be ready for use as fuel in gas turbines or internal combustion engines to generate electrical energy and/ or thermal energy. 8 As a result of growing environmental concern, gasification is gaining popularity as a means of generating hydrogen-rich producer gas for use in fuel cells to generate electricity or as a source of raw materials for the production of synthetic chemicals, liquid fuels like gasoline or methanol, and gaseous fuels like hydrogen, ammonia or methane. [9][10][11] Since hydrogen may be used as a fuel for fuel cells, as an energy carrier or a storage medium, and burnt directly as a fuel, it is seen as a potentially desirable option since it provides carbon-free power where it is used.…”
mentioning
confidence: 99%